The Role of Product Innovation in Increasing Business Competitiveness - Farida Akbarina; Sanita Dhakirah; Nurul Hidayatinnisa'; Becik Gati Anjari; Shohib Muslim (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The aim is to identify effective innovations for national companies so that their products remain high quality and relevant amidst increasingly fierce business competition. Through the narrative approach, researchers can deeply understand the experiences and perspectives related to product innovation needed. Product innovation is very important to increase the competitiveness of the food and beverage industry business. Innovation strategies include utilizing local raw materials, government support through incentives and policies, company investment in research and development, and community participation. The challenges are lack of government support, low investment, and limited quality human resources. Collaboration between the government, companies and the community is essential to create a conducive environment for innovation and improve Indonesia's economic competitiveness. Product innovation is critical to business competitiveness, especially in the food and beverage industry. Developing new products, improving existing products, and utilizing the latest technology can expand markets, increase customer loyalty, and create differentiation from competitors. Innovation includes not only new products, but also improvements in product quality, safety and convenience. Utilizing local raw materials can also improve Indonesia's economic competitiveness globally.